Avaliação físico-química da remediação de solos contaminados por BTEX - Lourenço, Edneia Santos de Oliveira (2006)
This research had as objective to evaluate the efficiency of the reactive means in the removal of aromatical hydrocarbons BTEX (Benzene, Toluene, Etil Benzene and Xylenes) in the ground, coming of leak of gasoline, either in fuel stations or underground tanks, and to explain the physico-chemical mechanisms that occuring on the system. The experiment was carried in laboratorial scale, in two types of permeable reactive barriers (PRB), called of AS (H2O2 + soil ) and ACA (H2O2 + activated coal) with the purpose to reduce the BTEX concentration through oxidation reaction or activated coal adsorption. For analysis of the efficiency of the barriers the BTEX concentrations in the sample of the gasoline when entering in the PRB and of the percolate in times of retention pre-established of 24, 36, 48, 60, 72 and 84 hours, using gas chromatography. The gotten results had shown that the two reactive barriers had reduced the BTEX concentration, being the ACA barrier the most efficient one. The effect has been attributed to the activated coal, which accomplishes the BTEX natural adsorption due to similarity in the polarity of its molecule with the BTEX composites, and still it acts as catalyst improving the oxidant action of hydrogen peroxide. The process, beyond to be efficient in the reduction of the BTEX concentrations, presents low cost and the advantage of the activated coal be regenerated.